German blood, Slavic soil : how Nazi Königsberg became Soviet Kaliningrad - Eaton, Nicole, 1979- (Battlegrounds (Ithaca, N.Y.), 2023)
"A history of Königsberg and Kaliningrad in the first half of the twentieth century, focusing on the region's political, social, and economic transformations under Nazi and Soviet rule and the violent encounter between the populations of both regimes"--